"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

Invisible work at work and the reproduction of gendered social service organizations - Lavee, Einat; Kaplan, Amit (Gender, Work and Organization, 2022)
Des études démontrent que la convergence du néolibéralisme et des impératifs de la nouvelle gestion publique crée des conditions dans lesquelles les prestataires de services sociaux entreprennent divers types de travail non rémunéré, réaffirmant le rôle du genre dans la prestation de services. En s’appuyant sur ces arguments, cette étude explore le processus par lequel les pratiques non rémunérées restructurent le genre dans les organisations de services sociaux, en utilisant le concept de « travail invisible ». En appliquant la méthode d’enquête de l’ethnographie institutionnelle, nous examinons les expériences des travailleurs des services sociaux dans le secteur public israélien et opérationnalisons le travail non rémunéré comme des ressources personnelles informelles que les travailleurs fournissent aux clients. L’analyse de 185 entretiens approfondis a révélé trois principaux cadres discursifs que les travailleurs utilisent pour justifier la fourniture de ressources personnelles. Grâce à ces cadres, les pratiques informelles deviennent invisibles en tant que travail à plusieurs niveaux – pour soi-même, pour l’organisation et pour la société. Tout comme le travail invisible dans le ménage, son invisibilité sur le lieu de travail constitue une force principale dans la reproduction des organisations de services sociaux sexuées.
Keywords: approches et analyses; asie; discipline; inégalités; israël; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible; travail social; éthnographie institutionnelle

Hosting overnight guests: Gendered unpaid work as a solidarity mechanism of migrants in the process of urbanization in Turkey - Uyar Mura, Elif S. (Social Politics, 2022)
This article addresses overnight guest hosting, which is a widespread solidarity practice among rural-to-urban migrants in Turkey. The fieldwork, based on in-depth interviews with 28 first-generation migrant women, reveals that it was mostly the young migrant women who shouldered hosting tasks as gendered unpaid work, which deepen their time poverty and reinforce their dependence on family. The analysis highlights the links between intersectional disadvantages of young migrant women and poverty, the failure of the welfare state to provide social assistance for migrants, and the familialist character of social policy during the peak years of migration. © 2022 The Author(s). Published by Oxford University Press.
Keywords: approches et analyses; asie; classisme; discipline; europe; femmes migrantes*; histoire et politique; intersectionnalité; pauvreté; projet charge mentale; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible; turquie